Matriz de Análise Politica Aplicada a Cadeia Produtiva da Manga no Município de Petrolina, Pernambuco - Araújo, William Bruno Cerqueira (2015)
The present study aimed to analyze the behavior of the production chain of mango exported to the United States, through the use of private and social indicators, from the perspective of Policy Analysis Matrix (PAM), in Petrolina-PE corridor to the port of Salvador; as well as the role of public policy on the studied chain. Thus, it presents a framework of Policy Analysis Matrix in order to provide theoretical and practical support to the research. Exploratory research was the guide to this study, applied by means of qualitative and quantitative approach and developed based on primary and secondary data associated with the case study that were structured through accounting matrices organized in spreadsheets developed using Excel - Microsoft 2010. These data were provided by cooperative mango producing companies, carriers, customs brokers and research institutions, and collected in the city of Petrolina-PE. The profitability related to the private and social costs and government policies, offered the concepts that underlie the analyzes performed in this study. The producers that have been studied in the case were divided in three groups. Six accounting matrices were calculated using data from three groups considering and excluding expenses on non-tariff barriers related to the fruit exportation to the US market. Thus, the analysis of the results shows that, in all the links of the chain, the private and social profitability and economic efficiency of the system are positive for all groups considering whether or not spending on non-tariff barriers, even occurring producer income transfer to society and taxation in the chain. Thereby, the three groups analyzed have competitive and comparative advantages, even with the performance of negative effects of public policies and non-tariff barriers imposed by the US government for the import of Brazilian mango. The presented competitiveness could be higher if there were the US import requirements. Consequently, the productive chain of mango aimed at exports has favorable prospects and expansion trend, despite the "discouragement".